2000
DOI: 10.1210/mend.14.5.0458
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of JAK/STAT (Janus Kinase/Signal Transducer and Activator of Transcription) in the Thyrotropin Signaling Pathway

Abstract: TSH is an important physiological regulator of growth and function in thyroid gland. The mechanism of action of TSH depends on interaction with its receptor coupled to heterotrimeric G proteins. We show here that TSH induces the phosphorylation of tyrosine in the intracellular kinases Janus kinase 1 (JAK1) and -2 (JAK2) in rat thyroid cells and in Chinese hamster ovary (CHO) cells transfected with human TSH receptor (TSHR). The JAK family substrates STAT3 (signal transducers and activators of transcription) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…Furthermore, besides PKA, both the PKC and the tyrosine-kinase cascade have been related to the control of thyroid cell growth (13). Recent evidence has also demonstrated the involvement of JAK/STAT in the TSH-signalling pathway (39). These data might, at least in part, explain the case-to-case variability that we observed and also the unexpected absence of CREB expression in a few cases.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, besides PKA, both the PKC and the tyrosine-kinase cascade have been related to the control of thyroid cell growth (13). Recent evidence has also demonstrated the involvement of JAK/STAT in the TSH-signalling pathway (39). These data might, at least in part, explain the case-to-case variability that we observed and also the unexpected absence of CREB expression in a few cases.…”
Section: Discussionsupporting
confidence: 56%
“…We found that the amount of STAT3 protein phosphorylated on serine 727 was increased in the Wnt-1 overexpressing stable transfectant W1 clone, when compared with nontransfected FRTL-5 cells or to a vector-transfected clone. The increase in Ser727 phosphorylation of STAT3 seems not to be through the TSH/cAMP-signaling pathway, as TSH induces phosphorylation at both sites, Tyr 705 and Ser 727 in FRTL-5 cells (Park et al 2000). As there is evidence for a role of PKC in serine phosphorylation of STAT3 (Jain et al 1999), it is plausible that the Wnt-1 activation of the Wnt/Ca CC pathway leading to PKC activation increased serine phosphorylation of STAT3 in the Wnt-1 overexpressing cell.…”
Section: Discussionmentioning
confidence: 94%
“…Gel-purified oligonucleotides were labeled with [␥-32 P]ATP using T4 polynucleotide kinase and purified on an 8% native polyacrylamide gel. EMSA was performed as previously described (26). Binding reactions in high salt with detergent were conducted in a solution of 1.5 fmol of 32 P-labeled DNA, 2 g of nuclear extract, and 0.5 g of poly(dI-dC) in 10 mM Tris-HCl (pH 7.9), 5 mM MgCl 2 , 50 mM KCl, 1 mM DTT, 1 mM EDTA, 0.1% Triton X-100, and 12.5% glycerol.…”
Section: Nuclear Extracts and Emsamentioning
confidence: 99%